Três auto-imagens de professoras dos anos iniciais da rede municipal de Santa Maria: aproximações da condição docente - Leal, Bettina Poglia (2007)
This essay is inserted into the research on the teacher s formation. It is a study where I have tried to come close to the imaginary regarding to self-image process. Three elementary school teachers were formally questioned about their lives considering both the personal as well as the professional aspects. It is a research using a qualitative approach involving life stories and memories of these three teachers/co-workers from The Municipal Elementary School System of Santa Maria. The interviews have been partly structured, recorded through tape recorder and divided into three different groups: the teacher as a human being; the teacher as a professional and, at last both their personal and professional lives as well as their interlacements. It was given time for the three teachers to be listened, such as the possibility for acting through their inner attention, standing easy to report a little from their personal and professional lives. At the beginning, I myself describe my personal history of life, my forthcomings to the topic and the motive of my choice. Afterwards, I present the teachers/co-workers, my colleagues and co-producer of this research. Following, I point out what the motive for the trajectory of this study, the purpose of the research and the thesis. Relevant aspects as time, the solitude of the scholar routine and the professional depreciation were observed and analyzed alongside the reports. There was no intention of generalizing the results but just to take it as a reference to rethink about our practices and attitudes in the world where we actuate, that is, the school. In such case we realize that the chosen subject, even much discussed in schools routine, seems to be not in accordance with the academic researches. This takes us to believe in the complexity of dimensions and contexts that build the images and self-images of teachers. To conclude, we believe that the teacher has the possibility of provoking transformations: liberty and responsibility are only possible from self-respect, where we can choose by ourselves, not only under external pressures